2021
DOI: 10.3390/clockssleep3010011
|View full text |Cite
|
Sign up to set email alerts
|

Comment Concerning the Effects of Light Intensity on Melatonin Suppression in the Review “Light Modulation of Human Clocks, Wake, and Sleep” by A. Prayag et al.

Abstract: Dose-response curves for circadian phase shift and melatonin suppression in relation to white or monochromatic nighttime illumination can be scaled to melanopic weighed illumination for normally constricted pupils, which makes them easier to interpret and compare. This is helpful for a practical applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…As a consequence, dose-response curves collected under undilated conditions [e.g., (43)] represent a mixture of two effects: a pupil size effect that modifies retinal light exposure, and a melatonin-suppressive effect. Special care must be taken when dose-response curves collected under different pupil conditions are compared (1,44).…”
Section: Pupil Sizementioning
confidence: 99%
“…As a consequence, dose-response curves collected under undilated conditions [e.g., (43)] represent a mixture of two effects: a pupil size effect that modifies retinal light exposure, and a melatonin-suppressive effect. Special care must be taken when dose-response curves collected under different pupil conditions are compared (1,44).…”
Section: Pupil Sizementioning
confidence: 99%
“…In their commentary, Bracke and colleagues [ 1 ] compare three melanopic irradiance-response curves that they derived from three studies where melatonin suppression was measured in response to either light at 460 nm (likely monochromatic), nine wavelengths (likely monochromatic), or fluorescent white light at 6500 K (see their Figure 1). Because the bibliographic references of the three studies were not reported, we cannot check whether these three studies were under the same experimental conditions (e.g., duration and timing of light exposure).…”
Section: Elements Of Context On the Importance Of Experimental Conditions And On Mathematical Modellingmentioning
confidence: 99%
“…Bracke and colleagues [ 1 ] are of the view that polychromatic lights likely need less melanopic irradiance than monochromatic light sources to elicit melatonin suppression, and to that purpose, they show such a comparison between monochromatic and polychromatic light sources in Figure 1 of their commentary. However, Brown [ 41 ], compiling data from 18 studies in which light exposures were either from monochromatic or polychromatic light sources, recently showed that most non-visual responses in humans (including circadian phase shifting, increased alertness, and melatonin suppression) can be best-modeled by a similar four-parameter melanopic irradiance-response model (although with different parameters, as shown in Prayag et al, 2019b) [ 2 ].…”
Section: Melatonin Suppression Depends On and Is Predicted By The Spectral Content In Melanopsin-weighted Irradiance Not On The Light Soumentioning
confidence: 99%
See 2 more Smart Citations